High-Fat Diet-Induced Alterations in the Feeding Suppression of Low-Dose Nisoxetine, a Selective Norepinephrine Reuptake Inhibitor - Nicholas T. Bello; Amy L. Walters; Jessica L. Verpeut; Priscila P. Cunha (Hindawi Limited, 2013)
Central noradrenergic pathways are involved in feeding and cardiovascular control, physiological processes altered by obesity. The present studies determined how high-fat feeding and body weight gain alter the sensitivity to the feeding suppression and neural activation to a selective norepinephrine reuptake inhibitor, nisoxetine. Acute administration of nisoxetine (saline: 0, 3, 10, and 30 mg/kg; IP) resulted in a dose-dependent reduction in the 24 h refeeding response in male Sprague Dawley rats maintained on standard chow. In a similar fashion, nisoxetine resulted in reductions in blood pressure and a compensatory increase in heart rate. From these studies, the 3 mg/kg dose was subthreshold. In a separate experiment, however, 10 wk exposure to a high-fat diet (60% fat) resulted in weight gain and significant feeding suppression following administration of nisoxetine (3 mg/kg) compared with animals fed a control diet (10% fat). Nisoxetine (3 mg/kg) also resulted in greater neural activation, as measured by c-Fos immunohistochemistry, in the arcuate nucleus of the hypothalamus in animals exposed to the high-fat diet. Such data indicate acute nisoxetine doses that suppress food intake can impact cardiovascular measures. It also suggests that the feeding suppression to a low-dose nisoxetine is enhanced as a result of high-fat diet and weight gain.